Forage yield of maize adapted to the humid tropic of Mexico - Sánchez Hernández, Miguel Angel; Cruz Vázquez, Manuela; Sánchez Hernández, César; Morales Terán, Gladis; Rivas Jacobo, Marco Antonio; Villanueva Verduzco, Clemente (Revista Mexicana de Ciencias Agrícolas, 2019)
A study was carried out in Loma Bonita, Oaxaca with the objective of evaluating the forage yield of maize genotypes adapted to the humid tropics of Mexico. The preparation of the land consisted of a fallow, tracing, crossed and furrowed, the establishment of the genotypes was on October 6, 2012, having as treatments six maize genotypes: NH-5, HE-1A17, VS-536, H -564C, DK-357 and H-520 that were distributed in a randomized block experimental design with divided plots and three replications, where the effect of three planting densities for each genotype was evaluated at 50 000, 62 500 and 83 333 plants ha-1. To estimate the differences between genotypes and sowing densities, the information was subjected to an analysis of variance and Tukey’s mean comparison test (p£ 0.05). At the time of harvesting the forage in January 2013, the characters plant height (Alp), male and female flowering (Dfm, Dff), leaf area (Aft), stem diameter (Dta), total leaves and leaves above of corn (Nho, Hae), cobs per plant (Epp), knots per plant (Npp), weight of leaves and stems (Pho, Pet), weight of corn with and without bracts (Peho, Pesh), length and diameter of corn (Lel, Delo), rows per corn, grains per row and grains per corn (Nhel, Ngh, Nge), weight of cobs (Pes) and yield in fodder (ren) were studied.. The results indicated that on average of three planting densities the genotypes VS-536 (38.8 t ha-1) and H-564C (36.6 t ha-1) excelled in forage production. The sowing density of 83 333 plants ha-1, in average of genotypes, produced the highest forage yield of 41.8 t ha-1. Considering the interaction of genotype by density, there was a high production of green biomass with the variety VS-536 (49.5 t ha-1) established at 83 333 plants ha-1.
Keywords: Gramineae; forage production; hybrids; synthetic variety